North American survey on impact of the COVID-19 pandemic shutdown on DBS care. (November 2021) - Siddiqui, Mustafa S.; Jimenez-Shahed, Joohi; Mari, Zoltan; Walter, Benjamin L.; De Jesus, Sol; Panov, Fedor; Schwalb, Jason M.; York, Michele K.; Sarva, Harini; Bertoni, John M.; Patel, Neepa; Zhang, Lin; et al.
Abstract: Background: The initial COVID-19 pandemic shutdown led to the canceling of elective surgeries throughout most of the USA and Canada. Objective: This survey was carried out on behalf of the Parkinson Study Group (PSG) to understand the impact of the shutdown on deep brain stimulation (DBS) practices in North America. Methods: A survey was distributed through RedCap® to the members of the PSG Functional Neurosurgical Working Group. Only one member from each site was asked to respond to the survey. Responses were collected from May 15 to June 6, 2020. Results: Twenty-three sites participated; 19 (83%) sites were from the USA and 4 (17%) from Canada. Twenty-one sites were academic medical centers. COVID-19 associated DBS restrictions were in place from 4 to 16 weeks. One-third of sites halted preoperative evaluations, while two-thirds of the sites offered limited preoperative evaluations. Institutional policy was the main contributor for the reported practice changes, with 87% of the sites additionally reporting patient-driven surgical delays secondary to pandemic concerns. Pre-post DBS associated management changes affected preoperative assessments 96%; electrode placement 87%; new implantable pulse generator (IPG) placement 83%; IPG replacement 65%; immediate postoperative DBS programming 74%; and routine DBS programming 91%. Conclusion: The COVID-19 pandemic related shutdown resulted in DBS practice changes in almost all North American sites who responded to this large survey. Information learned could inform development of future contingency plans to reduce patient delays in care under similar circumstances. Highlights: During the COVID-19 pandemic related shutdown, North American DBS sites experienced significant changes in all aspects of DBS practice. Telemedicine was heavily used for many outpatient DBS-related assessments across disciplines (neurology, neurosurgery and neuropsychology). This paper highlights the need for contingency plans at DBS sites to continue care of DBS patients in case of another similar shutdown and identifies areas for future research related to the remote care of DBS patients.